MiR‐27a‐3p targets USP46 to inhibit the cell proliferation of hepatocellular carcinoma. (30th May 2022) - Wen, Minghua; Xu, Hongyan; Peng, Hong; Sheng, Yanling; Yang, Wenlong; Yan, Jinlong
Abstract: Micro‐RNAs are involved in the occurrence and development of hepatocellular carcinoma (HCC) as potential therapeutic targets for HCC. In this study, we found that miR‐27a‐3p was highly expressed in HCC, which was associated with lower survival rates of HCC patients. In vivo and in vitro functional experiments confirmed that over‐expression or knock‐down miR‐27a‐3p could significantly affect the proliferation ability of HCCLM3 and Huh‐7, two HCC cell lines. Ubiquitin‐specific protease 46 (USP46) was confirmed as the key target gene of miR‐27a‐3p in HCC via RNA‐seq, quantitative polymerase chain reaction, Western blotting, and luciferase report. When knocking down USP46, the proliferation activity of HCC cells was significantly enhanced, while it was significantly inhibited after over‐expressing USP4. Above results suggest that the abnormally over‐expressed miR‐27a‐3p in liver promotes the proliferation of cancer cells and accelerates the development of HCC by targeting inhibition the expression of USP46. Targeting miR‐27a‐3p may be an effective strategy for prevention and treatment of HCC. Abstract : MiR‐27a‐3p highly expresses in hepatocellular carcinoma (HCC) and is associated with low survival rate. MiR‐27a‐3p. MiR‐27a‐3p targets regulating the expression of USP46 to promote cell proliferation of HCC.